Irrigation mitigates the heat impacts on photosynthesis during grain filling in maize - Xing-long WANG; Yu-peng ZHU; Ye YAN; Jia-min HOU; Hai-jiang WANG; Ning LUO; Dan WEI; Qing-feng MENG; Pu WANG (Journal of Integrative Agriculture, 2023)
Elevating soil water content (SWC) through irrigation was one of the simple mitigation measures to improve crop resilience to heat stress. The response of leaf function, such as photosynthetic capacity based on chlorophyll fluorescence during the mitigation, has received limited attention, especially in field conditions. A two-year field experiment with three treatments (control treatment (CK), high-temperature treatment (H), and high-temperature together with elevating SWC treatment (HW)) was carried out during grain filling with two maize hybrids at a typical station in North China Plain. Averagely, the net photosynthetic rate (Pn) was improved by 20%, and the canopy temperature decreased by 1–3°C in HW compared with in H in both years. Furthermore, the higher SWC in HW significantly improved the actual photosynthetic rate (Phi2), linear electron flow (LEF), variable fluorescence (Fv), and the maximal potential quantum efficiency (Fv/Fm) for both hybrids. Meanwhile, different responses in chlorophyll fluorescence between hybrids were also observed. The higher SWC in HW significantly improved thylakoid proton conductivity (gH+) and the maximal fluorescence (Fm) for the hybrid ZD958. For the hybrid XY335, the proton conductivity of chloroplast ATP synthase (vH+) and the minimal fluorescence (Fo) was increased by the SWC. The structural equation model (SEM) further showed that SWC had significantly positive relationships with Pn, LEF, and Fv/Fm. The elevating SWC alleviated heat stress with the delayed leaf senescence to prolong the effective period of photosynthesis and enhanced leaf photosynthetic capacity by improving Phi2, LEF, Fv, and Fv/Fm. This research demonstrates that elevating SWC through enhancing leaf photosynthesis during grain filling would be an important mitigation strategy for adapting to the warming climate in maize production.